Determinan Kesulitan Berhenti Merokok Berdasarkan Pengaruh Keluarga, Teman Sebaya, Dan Lingkungan Terhadap Paparan Rokok Pada Anak Smp Serta Sma Di Indonesia - Welly Welly; Vebby Amelia Edwin; Adela Resa Putri (Universitas Sumatera Barat, 2025)
Difficulties in quitting smoking among adolescents represent an increasingly complex public health challenge, particularly in countries with a high prevalence of tobacco use such as Indonesia. This study aims to analyze the determinants of smoking cessation difficulty among junior and senior high school students using data from the 2019 Indonesia Global Youth Tobacco Survey (GYTS). The study employed bivariate and multivariate logistic regression analyses, incorporating survey weights, stratification, and cluster effects. The findings indicate that 79.58% of adolescent smokers experience difficulty quitting. Significant factors associated with increased likelihood of cessation difficulty include having smoking parents (OR 1.31), being offered cigarettes by peers (OR 1.32), being female (OR 2.17), older age (OR 1.68–2.07), and exposure to smoking at school (OR 1.18). Conversely, exposure to smoking at home was not significantly associated with cessation difficulty. These results emphasize the need for comprehensive adolescent smoking cessation efforts that integrate family involvement, smoke-free school environments, and social-support–based interventions. Understanding the factors that hinder adolescents’ ability to quit smoking enables the development of more effective tobacco control strategies to protect youth from long-term addiction risks.